Fabrication and Properties of a Biomimetic Dura Matter Substitute Based on Stereocomplex Poly(Lactic Acid) Nanofibers - Chuan D (Dove Medical Press, 2020)
Di Chuan,* Yuelong Wang,* Rangrang Fan, Liangxue Zhou, Haifeng Chen, Jianguo Xu, Gang Guo State Key Laboratory of Biotherapy and Cancer Center and Department of Neurosurgery, West China Hospital, Sichuan University, and Collaborative Innovation Center for Biotherapy, Chengdu 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Guo; Liangxue ZhouState Key Laboratory of Biotherapy and Cancer Center, and Department of Neurosurgery, West China Hospital, Sichuan University, and Collaborative Innovation Center for Biotherapy, No. 17, Block 3, Southern Renmin Road, Chengdu 610041, People’s Republic of ChinaTel +86 28-8516 4063Fax +86 28 85164060Email guogang@scu.edu.cn; liangxue_zhou@126.comBackground: Duraplasty is one of the most critical issues in neurosurgical procedures because the defect of dura matter will cause many complications. Electrospinning can mimic the 3D structure of the natural extracellular matrix whose structure is similar to that of dura matter. Poly(L-lactic acid) (PLLA) has been used to fabricate dura matter substitutes and showed compatibility to dural tissue. However, the mechanical properties of the PLLA substitute cannot match the mechanical properties of the human dura mater.Methods and Results: We prepared stereocomplex nanofiber membranes based on enantiomeric poly(lactic acid) and poly(D-lactic acid)-grafted tetracalcium phosphate via electrospinning. X-ray diffraction results showed the formation of stereocomplex crystallites (SC) in the composite nanofiber membranes. Scanning electron microscope observation images showed that composites nanofibers with higher SC formation can keep its original morphologies after heat treatment, suggesting the heat resistance of composite nanofiber membranes. Differential scanning calorimeter tests confirmed that the melting temperature of composite nanofiber membranes was approximately 222°C, higher than that of PLLA. Tensile testing indicated that the ultimate tensile strength and the elongation break of the stereocomplex nanofiber membranes were close to human dura matter. In vitro cytotoxicity studies proved that the stereocomplex nanofiber membranes were non-toxic. The neuron-like differentiation of marrow stem cells on the stereocomplex nanofiber membranes indicated its neuron compatibility.Conclusion: The stereocomplex nanofiber membranes have the potential to serve as a dura mater substitute.Keywords: poly(lactic acid), dura matter substitute, stereocomplex crystallites, electrospinning